Variation of picture angles and its effect on the Concealed Information Test - Ann Hsu; Yu-Hui Lo; Shi-Chiang Ke; Lin Lin; Philip Tseng (Cognitive Research, 2020)
Abstract Background The reaction time-based Concealed Information Test (RT-CIT) is a memory paradigm used to detect crime-related knowledge. However, this would also imply that the RT-CIT would be vulnerable to factors that are known to compromise object recognition or memory integrity. From this perspective, one key issue is whether “guilty” memory can be detected if the crime-related images are photographed at different angles from what the perpetrator saw, which is almost always the case in the field. To investigate this, here we manipulated the deviation angles, from 0° to 330° in 11 steps, between the study and test phases to assess how the RT-CIT holds up against angular rotations. Results We observed a robust RT-CIT effect at all deviation angles for both deep-encoders (Experiment 1) and shallow-encoders (Experiment 2). The RT-CIT was effective within the first 250 or so trials for both encoding groups, with smaller probe-irrelevant differences beyond that. Conclusions With appropriate encoding and memory strength, RT-CIT images do not necessarily have to match the exact angle of the perpetrator’s perspective at the time of the crime. Unnatural angles such as 90° and 270° or unconventional rotational axes may require caution. Trial number under 250 trials show maximal Probe-Irrelevant difference, but more trials may add power to improve detection accuracy.